Evaluation of the efficacy of Superior Cluneal Nerve Block in low back pain: A prospective observational study. (April 2022) - Gautam, Sujeet; Gupta, Navneet; Khuba, Sandeep; Agarwal, Anil; Kumar, Sanjay; Das, Pravin Kumar
Abstract: Introduction: Superior cluneal nerve (SCN) entrapment giving rise to low back pain (LBP) remains undiagnosed many times; in this clinical study authors have evaluated therapeutic role of lidocaine injection of SCN for low back pain relief in patients with SCN entrapment. Methods: The present study was a prospective, observational study; 25 patients with unilateral LBP over the iliac crest and buttock for more than six months not responding to conservative measures were included in this clinical trial. SCN lidocaine injection was done under fluoroscopy guidance; patients having more than 50% reduction in numeric rating scale (NRS) score, for at least 2 h following SCN injection, were enrolled in the study and followed for 6 months. The primary outcome measure was severity of LBP, measured by NRS score. Secondary outcome measures were percentage pain relief; Oswestry Disability Index (ODI) score, reduction of analgesic usage, DSM-IV score for psychological assessment. All these assessments were done prior to the procedure and at 2 weeks, 1, 3 and 6 months after the procedure. Results: A significant reduction in the NRS scores was observed at 2 weeks, 1, 3 and 6 months after SCN lidocaine injection as compared to the baseline (P value < 0.05); authors also observed a significant pain relief and significantly reduced ODI scores, analgesic consumption and DSM scores compared to the baseline values (P value < 0.05). Conclusion: A single SCN lidocaine injection provided significant pain relief in LBP patients with SCN entrapment for a period of 6 months.